PELATIHAN VISUAL BRANDING DAN COREL DRAW BAGI PELAKU UMKM DI KECAMATAN GEDONG TATAAN. - Ade Moussadecq; Abdi Darmawan; Muhammad Redintan Justin; Rohiman Rohiman; Desiana Muryasari (Institut Informatika dan Bisnis Darmajaya, 2022)
This visual branding training for UMKM prioritizes the crucial role of logos as the main component of visual branding for product marketing activities for benefits and how to design a logo that is easy to remember in accordance with logo principles so that the logo can give a memorable impression to potential consumers. The achievement of this activity is how the future training participants will know and be able to produce logo designs that represent the image of their business. Presentation of visual branding materials using presentation, discussion and practice methods. Presentations are used when the service team explains the function of visual branding and its components such as logos, taglines and promotional strategies. In the stage of introducing the graphics application, the service team gave the Corel Draw module to the trainees. The first day of the training, after the presentation of the material, the service team immediately installed the application on the trainees who brought laptops. The service team asked participants to understand and study the tools in Corel Draw in accordance with the content of the modules that have been given. Keywords— Trainning, Visual Branding, Gedong Tataan.